(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
There is a great need for safe living and travel in this age of rapidly developing technology. The number of cars on the road has risen steadily during the previous decade. As the number of vehicles on the road continues to soar, keeping tabs on each one becomes an increasingly difficult chore. In this study, we propose using roadside surveillance cameras to implement an automated vehicle tracking system for high-velocity vehicles. Obtaining CCTV video of a live event is a time-consuming operation. You Only Look Once (YOLO), a deep learning model used for object recognition, is utilised to address this issue. There are essentially four stages to the suggested process.